Analysis of Presentation and Reporting of Financial Transactions in the Pulau Harapan Cooperative, Agam District - Nasfizar GUSPENDRI; Nita FITRIA (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to analyze the presentation and reporting of financial transactions at the Pulau Harapan Cooperative, Agam Regency. As well as analyzing the extent to which the presentation is in accordance with sharia principles and applicable accounting standards. The research method used is qualitative with a case study approach. Data was obtained through in-depth interviews, observation and analysis of cooperative financial documents. This research uses data originating from daily financial transactions at the Pulau Harapan Cooperative, Agam Regency. Data is analyzed and processed to produce financial reports based on the Sharia Financial Accounting Standards (PSAK). The results of the research concluded that cooperative financial transactions, which only take the form of daily transactions, can already prepare financial reports based on the Sharia Financial Accounting Standards (PSAK) and produce financial reports for each business unit as well as consolidated financial reports